Perspectives of key stakeholders on employment of autistic adults across the united states, australia, and sweden. Issue 11 (5th July 2019) - Black, Melissa H.; Mahdi, Soheil; Milbourn, Benjamin; Thompson, Craig; D'Angelo, Axel; Ström, Eva; Falkmer, Marita; Falkmer, Torbjörn; Lerner, Matthew; Halladay, Alycia; Gerber, Alan; Esposito, Christopher; et al.
Abstract : Despite efforts to improve employment outcomes for autistic individuals, internationally their employment rates remain low. There is a need to better understand the factors influencing successful employment for autistic adults in the labor market from the perspectives of multiple key stakeholders. This study represents the second in a series of papers conducted as part of an International Society for Autism Research policy brief aimed at improving employment outcomes for autistic individuals. A community consultation methodology using focus groups, forums, and interviews was applied with autistic individuals ( n = 19), family members ( n = 18), service providers ( n = 21), employers ( n = 11), researchers ( n = 5), and advocacy group representatives ( n = 5) in Australia, Sweden, and the United States, aiming to identify the factors perceived to determine gaining and maintaining employment for autistic individuals. Directed content analysis, guided by the International Classification of Functioning, Disability and Health (ICF), was conducted to investigate the key factors influencing employment outcomes for autistic individuals. Meaningful verbal concepts, or units of text with common themes, were also derived from the qualitative data and then linked and compared to the ICF Autism Spectrum Disorder (ASD) Core‐sets. Across countries, activity and participation and environmental factor categories of the ICF were the most associated with employment outcomes. Results suggest that removal of environmental barriers and enhancing environmental facilitators may assist to remediate ASD‐related difficulties in the workplace. Autism Res 2019, © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This study sought to understand the perspectives of autistic individuals and key stakeholders on factors influencing if autistic adults get and keep jobs. Across Australia, Sweden, and the United States, focus groups and interviews were conducted to understand international perspectives on what helps and hinders getting and keeping a job for autistic individuals. The environment, including supports, relationships, attitudes, and services, were perceived to be the most important for workplace success. Intervention targeting barriers and facilitators in the workplace environment may support autistic adults to be successful in the labor market.